Performing ethnomusicology teaching and representation in world music ensembles (Univ. of California Press, 2004)
'Performing Ethnomusicology' is the first book to deal exclusively with creating, teaching, & contextualizing academic world music performing ensembles. 16 essays discuss the problems of public performance & the pragmatics of pedagogy & learning processes.